Approximate analytical solutions to the condensation-coagulation equation of aerosols. Issue 6 (2nd June 2016) - Smith, Naftali R.; Shaviv, Nir J.; Svensmark, Henrik
ABSTRACT: We present analytical solutions to the steady state nucleation-condensation-coagulation equation of aerosols in the atmosphere. These solutions are appropriate under different limits but more general than previously derived analytical solutions. For example, we provide an analytic solution to the coagulation limit plus a condensation correction. Our solutions are then compared with numerical results. We show that the solutions can be used to estimate the sensitivity of the cloud condensation nuclei number density to the nucleation rate of small condensation nuclei and to changes in the formation rate of sulfuric acid. © 2016 American Association for Aerosol Research